2011
DOI: 10.1111/j.1600-0625.2011.01273.x
|View full text |Cite
|
Sign up to set email alerts
|

Survivin in skin pathologies

Abstract: Survivin is a member of the inhibitor of apoptosis (IAP) protein family acting at the intersection between proliferation and cell survival. This protein exhibits low or undetectable expression in most adult tissues but is increased in the majority of cancers. Suggested to be one of the most cancer-specific proteins identified to date, survivin acts as a signalling node in tumour maintenance and, after first promising results, is now attracting increasing attention as a target in anti-cancer therapy. In the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 149 publications
4
32
0
3
Order By: Relevance
“…In the present study, highest levels of expression of nuclear p53 were significantly associated with a shorter post surgical OS, and appeared to be related to the development of metastasis, confirming the importance of p53 as a negative prognostic marker in canine OSA, in accordance to previous published data regarding canine OSA, suggesting that, similarly to human OSA [68,69], alterations in p53 functions are associated with highly aggressive tumour behaviour [70,71]. Deregulation of the p53-survivin subsystem has been proposed to play an important role in several tumour types [72], since, WTp53 is able to repress survivin expression at both the mRNA and protein level [40]. In spite of this, our results suggests that different mechanisms could regulate survivin expression in canine OSA.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In the present study, highest levels of expression of nuclear p53 were significantly associated with a shorter post surgical OS, and appeared to be related to the development of metastasis, confirming the importance of p53 as a negative prognostic marker in canine OSA, in accordance to previous published data regarding canine OSA, suggesting that, similarly to human OSA [68,69], alterations in p53 functions are associated with highly aggressive tumour behaviour [70,71]. Deregulation of the p53-survivin subsystem has been proposed to play an important role in several tumour types [72], since, WTp53 is able to repress survivin expression at both the mRNA and protein level [40]. In spite of this, our results suggests that different mechanisms could regulate survivin expression in canine OSA.…”
Section: Discussionsupporting
confidence: 81%
“…One of the most important aspects of the study of survivin expression in cancer is related to its high cancer specificity and consequent potential role as therapeutic target [37,38]. Survivin has been identified as a target gene of the β-catenin pathway [39], and it acts as a cell cycle regulator and apoptosis inhibitor, even if different isoforms with different functions of the molecule have been described [40]. …”
Section: Introductionmentioning
confidence: 99%
“…Similarly to the proliferation marker Ki-67 (Gilhar et al , 2004), N-surv-positive cells are more numerous in the epidermis from young individuals than from adult individuals. However, not all N-surv-expressing cells stain for Ki-67 in human cancerous skin (Bongiovanni et al , 2011). In addition, in the normal skin, Ki-67-positive cells are usually located in the basal layer of normal epidermis, whereas N-surv-positive cells are also detected in suprabasal layers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there were 10 genes in the survivin network significantly up-regulated in PIS compared to other tissues. Because survivin is an inhibitor of apoptosis [59], up-regulated expressions of genes in this network may render the cells more resistant to apoptosis, which may in turn facilitate persistent infection. Studies conducted by Zhang and Alexandersen [60] and Zhang et al [61] showed that declining rate of FMDV levels during early infection rather than the virus levels determined FMDV persistent infection.…”
Section: Discussionmentioning
confidence: 99%